2015
DOI: 10.1038/bmt.2014.322
|View full text |Cite
|
Sign up to set email alerts
|

Successful mobilization of PBSCs predicts favorable outcomes in multiple myeloma patients treated with novel agents and autologous transplantation

Abstract: Incorporation of novel agents into auto-SCT for patients with multiple myeloma has led to improvement in their outcomes. However, the effects of new drugs, either single or combined, on PBSC mobilization have not been fully evaluated, particularly in phase 3 clinical studies. We analyzed the impact of two novel agent-based induction treatments in patients enrolled in the GIMEMA MMY-3006 study comparing bortezomib, thalidomide and dexamethasone (VTD) versus thalidomide and dexamethasone (TD) in preparation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
2
19
0
2
Order By: Relevance
“…Importantly, this work validates the findings from the phase 3, open‐label, multicenter GIMEMA MMY‐3006 (NCT01134484) study published in 2015. This trial assessed the efficacy and safety of VTD versus TD induction therapy prior to ASCT and reported that poor mobilizers experienced inferior outcomes, defined as 5‐year rates of time to progression (TTP), PFS, and OS, relative to those that readily mobilized PBSCs …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, this work validates the findings from the phase 3, open‐label, multicenter GIMEMA MMY‐3006 (NCT01134484) study published in 2015. This trial assessed the efficacy and safety of VTD versus TD induction therapy prior to ASCT and reported that poor mobilizers experienced inferior outcomes, defined as 5‐year rates of time to progression (TTP), PFS, and OS, relative to those that readily mobilized PBSCs …”
Section: Discussionmentioning
confidence: 99%
“…This trial assessed the efficacy and safety of VTD versus TD induction therapy prior to ASCT and reported that poor mobilizers experienced inferior outcomes, defined as 5-year rates of time to progression (TTP), PFS, and OS, relative to those that readily mobilized PBSCs. 24 Although retrospective, our analysis has few positive aspects that is usually lacking in prospective studies. Because our dataset includes patients that were followed at our institution over a 10-year period, we were able to capture a wide range of induction regimens and salvage therapies, as well as their impact on PBSC mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Western countries the number of new cases of MM is 5.9 per 100,000 people per year and the median age at diagnosis is 69 years . MM is still an incurable disease and novel therapeutic drugs are required to treat patients . Monoclonal antibodies (mAbs) may improve MM treatment, similarly to other haematological malignancies.…”
mentioning
confidence: 99%